THE USE OF QUANTITATIVE RESEARCH METHOD AND STATISTICAL DATA ANALYSIS IN DISSERTATION: AN EVALUATION STUDY - Disman, Disman; Ali, Mohammad; Syaom Barliana, M. (International Journal of Education, 2017)
Writing a dissertation is one of the requirements every postgraduate student has to accomplish in completing his/her doctorate program; and it is written based on research. This study addresses the problem concerning the pattern of weaknesses in the students’ research, particularly related to the use of research and statistical methods. Its objectives are to explore the weakness pattern of their research method and statistical data processing and analyze various causes of the pattern. The study is focused on the dissertations written by Universitas Pendidikan Indonesia’s School of Postgraduate Studies’ students that used a quantitative approach based on the review undertaken by the school’s commission from academic year 2012/2013 to 2013/2014. The study employed a qualitative approach and data analysis was done by using logical analysis of the review results. Findings of the study indicate there are various weaknesses in the students’ dissertations, particularly related to the way of thinking and inappropriate use of research method and statistical method. Inappropriate population, bias sampling technique, and inappropriate data analysis process and hypothesis testing are also found in the dissertations.